John Ambler papers - Ambler, John, 1762-1836.
Correspondence and other papers relating chiefly to Ambler's service in the Virginia Militia, especially in the 19th and 2nd regiments, during the period 1807-1822. Correspondents include William H. Cabell, John H. Cooke, Augustine Davis, George Dixon, John S. Pleasants, and George W. Smith.
Planter and militia officer.
Collection material in English.
Keywords: Cabell, William H., -- 1772-1853 -- Correspondence; Cooke, John H. -- Correspondence; Davis, Augustine, -- -1825 -- Correspondence; Dixon, George, -- 1755?-1800 -- Correspondence; Pleasants, John S. -- Correspondence; Virginia. -- Militia; Smith, George W. -- Correspondence; Militia officers; Plantation owners